Signing Up GME to English Learning in Boosting Students’ Oral Communication Performance - Aeni, Nur; K, Baharuddin; Diana, Sri; Bahang, M Dahlan; Dzhelilov, Akhtem A (ETERNAL (English, Teaching, Learning and Research Journal), 2024)
The study investigated whether or not students are interested in learning General Maritime English course materials and demonstrate how using General Maritime English course materials significantly increases students' success in oral communication. In this work, an experimental design was used. The researchers conducted nearly non-equivalent group design experiments for this investigation. For the second half of the academic year 2022/2023, 42 students were a part of the research group. Basic random sampling techniques were used in this investigation on a sample of clusters. Both an oral student communication exam and a student interest questionnaire were used to collect the data. Descriptive and inferential statistics were used to examine the student oral communication data, and the Likert scale was used to assess the student interest data. The study's findings were as follows: (1) The GME course materials might improve AMI AIPI's oral communication in Makassar's third semester. It can be said that GME training resources are effective at improving oral communication in terms of accuracy, fluency, and comprehension and that students are very interested in learning from GME language course materials at maritime academies. Signing up GME for Maritime English learning has the potential to significantly boost students' oral communication performance by providing an engaging, realistic, and effective learning environment. It can enhance language skills, cultural awareness, and overall communication competence, preparing students for successful careers in the maritime industry. As the implications of this study, enrolling in General Maritime English emphasizes the value of contextualized language instruction by improving students' oral communication skills. GME may greatly improve students' capacity for professional and effective communication in the marine industry by concentrating on industry-specific needs. This will improve safety, compliance, and career opportunities. But for these programs to be successful, they must handle the issues of resource allocation, varied student needs, and efficient assessment.